Computer Supported Collaborative Learning for Developing Higher Order Thinking Skill in ELT (International Journal of Multidisciplinary Perspectives in Higher Education, 2021)
The practice of integrating pedagogical approaches using multimedia technologies has become one of the common interests in the field of English language teaching (ELT) in recent years. This research study attempts at studying the characteristics of computer-supported collaborative learning (CSCL) tasks used for developing students' cognitive skills within the CSCL approach in the context of ELT in higher secondary school education in Nepal. Non-participant observation of the CSCL tasks assigned to the students in the English class in two different schools, and semi-structured interviews with the students were used as the research tools. It was found that the CSCL tasks were useful for enhancing some cognitive skills of the students, though many of the CSCL tasks assigned gave more attention to enhance the students' lower order thinking skills rather than their higher order thinking skills.